2007
DOI: 10.1192/apt.bp.107.003749
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence: treating abuser and abused

Abstract: Intimate partner violence is associated with significant psychiatric comorbidity. Treatment has focused on male perpetrators but recent studies indicate that this is of limited success in reducing male violence. This article reviews the current available treatments from three perspectives: that of the victim, the perpetrator, and the couple who wish to remain together. It also provides guidelines to assist the general psychiatrist in determining what treatment to offer patients who present with intimate partne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 37 publications
1
15
0
1
Order By: Relevance
“…A violência contra a mulher é um fenômeno de grande magnitude, motivo pelo qual tem sido considerada como um problema de saúde pública e como uma questão de violação dos direitos humanos (Joachim, 2000;Campbell, 2002;Heru, 2007;Schraiber e d'Oliveira, 2008) tanto por sua elevada incidência, como pela gravidade das consequências negativas para as vítimas e para seus familiares. Está presente no mundo todo, não respeita fronteiras de classe social, raça/etnia, religião, idade ou grau de escolaridade.…”
Section: Introductionunclassified
“…A violência contra a mulher é um fenômeno de grande magnitude, motivo pelo qual tem sido considerada como um problema de saúde pública e como uma questão de violação dos direitos humanos (Joachim, 2000;Campbell, 2002;Heru, 2007;Schraiber e d'Oliveira, 2008) tanto por sua elevada incidência, como pela gravidade das consequências negativas para as vítimas e para seus familiares. Está presente no mundo todo, não respeita fronteiras de classe social, raça/etnia, religião, idade ou grau de escolaridade.…”
Section: Introductionunclassified
“…and domestic violence has recently received substantial research providing a plethora of studies and findings [51]. While it is crucial to mention that no study has been able to demonstrate a causal link between psychopathology and violence that can be generalized to the public [52], numerous reasons as to why this is the case exist. Firstly, the studies that have found links to psychopathology and violence have used participants that have either been arrested for their offences or attend treatment programs.…”
Section: Psychological Theories Of Domestic Violencementioning
confidence: 99%
“…Others made the same conclusion regarding the links between IPV and depression (Arias, Lyons, & Street, 1997;Bonomi, Anderson, Rivara, & Thompson, 2007;Fedovskiy, Higgins, & Paranjape, 2008;Fogarty, Fredman, Heeren, & Liebschutz, 2008;Heru, 2007;Koopman et al, 2007;Leiner, Compton, Houry, & Kaslow, 2008;Sullivan, Meese, Swan, Mazure, & Snow, 2005;Tadegge, 2008;Van Hook, 2000) and between IPV and post-traumatic stress symptoms (DeJonghe, Bogat, Levendosky, & von Eye, 2008;Fedovskiy et al, 2008;Humphreys & Joseph, 2004;Scheffer Lindgren & Renck, 2008;Sullivan et al, 2005). Other effects of IPV on mental health include hypervigilance, flashbacks, nightmares, and loss of personal control (Wittenberg, Joshi, Thomas, & McCloskey, 2007).…”
Section: Impacts Of Ipv On Womenmentioning
confidence: 92%
“…Moreover, anger and aggression are involved with IPV (Cavell & Malcolm, 2007), as are the need for intimacy between the two partners and emotional distance (Doumas, Pearson, Elgin, & McKinley, 2008). Furthermore, Heru (2007) argued the constant threat of violence might strengthen the bond between the two partners because it brings them together against the violence. Wade (1997), in his book regarding the interplay between oppression and resistance, claimed the nature of human resistance and resilience exists in relationships that have violence and control.…”
Section: Definition and Types Of Ipvmentioning
confidence: 99%
See 1 more Smart Citation